2019
DOI: 10.1111/bjhp.12356
|View full text |Cite
|
Sign up to set email alerts
|

Examining the theory‐effectiveness hypothesis: A systematic review of systematic reviews

Abstract: Purpose Health interventions based on theory may be more effective than those that are not. This review of reviews synthesizes all published randomized controlled trial (RCT) meta‐analytic evidence from the last decade to examine whether theory‐based interventions were found to be associated with more effective adult health behaviour change interventions. Methods Systematic reviews including meta‐analyses were identified by searching Medline, CINAHL, PsycINFO, and CDSR. A narrative synthesis was used to summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 42 publications
1
71
0
2
Order By: Relevance
“…This requires further investigation particularly in light of the lack of associations between delivery features and weight effects found in this review. Although theory use was not found to be associated with more effective interventions, in line with previous evidence, a better understanding of the mechanisms through which SMS work is critical to optimise SMS effectiveness, including form of delivery and SMS content features. Limited information on how SMS interventions were developed was reported.…”
Section: Discussionsupporting
confidence: 60%
“…This requires further investigation particularly in light of the lack of associations between delivery features and weight effects found in this review. Although theory use was not found to be associated with more effective interventions, in line with previous evidence, a better understanding of the mechanisms through which SMS work is critical to optimise SMS effectiveness, including form of delivery and SMS content features. Limited information on how SMS interventions were developed was reported.…”
Section: Discussionsupporting
confidence: 60%
“…Of these, three had an explicit theoretical basis: Baby Milk Trial—Social Cognitive Theory, Healthy Beginnings—Health Belief Model and Social Learning Theory, and INSIGHT—Responsive Parenting . It should be noted that although interventions may not explicitly state an underlying theory, these interventions are likely to be guided by an implicit theory underpinning the selection of BCTs …”
Section: Discussionmentioning
confidence: 99%
“…Such information could assist in the testing and scale‐up of interventions. Interventions based on theory are more likely to be effective, however, some studies have found that this is not the case due to methodological and reporting issues . Importantly also, use of theory enables us to hypothesize and test how our interventions actually work, specifying the proposed causal mechanisms and the key intervention components or “behaviour change techniques” (BCTs) .…”
Section: Introductionmentioning
confidence: 99%
“…Although interventions based on theory are more likely to be effective, there are several theory-related and methodological issues that may hinder this (eg, inaccuracy of the theory itself, or not fully using the theory). 25 However, without theory we cannot hypothesise how and why behaviours could change, decide which tools or techniques may be useful in changing behaviour, or understand why an intervention has succeeded or (more often) failed in initiating and maintaining behaviour change. In practical terms,…”
Section: Use Of Theorymentioning
confidence: 99%